Accurate reduction of medial arch fracture fragments in intertrochanteric fractures: A novel technical note - Li, Xiaodong; Zhao, Chen; Sun, Guantong; Liu, Pengcheng; Tang, Jian; Yang, Fei; Wang, Xiaoqing (Frontiers in Surgery, 2023)
Intramedullary fixation is currently used to stabilize intertrochanteric fractures. Surgical reduction of the medial arch cortex is crucial to achieve stabilization of the internal fixation system, however, it is challenging to perform. To ensure anatomical reduction, we developed a novel surgical technique to assist in achieving accurate and convenient reduction. In this technique, right-angle forceps were used to pry and reset medial arch cortex fragments via a mini-helical blade incision. Noteworthily, all patients who underwent this technique achieved anatomical reduction with reduced operation times and bleeding. Our article illustrates intraoperative reduction techniques and summarizes tips and tricks that may be beneficial and educative for orthopedists.